The FASB's Policy of Extended Adoption for New Standards: An Examination of FAS No. 87. - Langer, Russell; Lev, Baruch (The Accounting Review, 1993)
Abstract A multi-year adoption period now appears to be the norm for new accounting standards issued by the Financial Accounting Standards Board (FASB). For example, FAS No. 52, which pertained to foreign currency, was issued in December 1981 and became effective in 1983, a three-year adoption period. FAS No. 71, which concerned regulation, was issued in December 1982, but became effective in 1984. FAS No. 87 on pensions was issued in December 1985 and became effective in 1987, but a key provision of this statement–the recognition of a "minimum liability"–became effective only in 1989, thereby allowing a five-year adoption period. FAS No. 96 on income taxes was issued in December 1987, but amendments under FAS Nos. 100 and 103 extended its adoption to 1990 and then to 1992, a six-year adoption period (ultimately, FAS No. 109 substantially changed FAS No. 96 and its successors). Although several early statements (e.g., FAS Nos. 2 and 8) issued late in the calendar year allowed adoption over that year and the following one, practically all FASB statements issued in the 1970s became effective on a uniform date close to their issuance. Thus, it appears that the FASB changed its adoption policy in the 1980s. The Board's main justification for an extended adoption period Is to alleviate firms' implementation costs, particularly the costs of renegotiating agreements with lenders and suppliers (see, e.g., FAS No. 52, par. 147-48, and FAS No. 87 par. 259-60). Interestingly, no justification was offered for the extended adoption period of FAS No. 96 (Income Taxes), perhaps an indication that a three-year adoption period had become a norm. However, when a fourth year was added under FAS No. 100, the following rationale was given (FASB 1988, par. 8): The Board believes that the disadvantages to preparers from not having a deferral of the effective date outweigh the disadvantages to users from a one-year delay in the required adoption of Statement 96, including diversity in financial reporting from the continued application of Opinion 11 by some enterprises. Given the obvious costs imposed by an extended adoption period on financial statement users, because of reduced cross-company comparability, the FASB's policy warrants scrutiny. This is the objective of the current study which focuses on FAS No. 87 (FASB 1985a) and the related FAS No. 88 (FASB 1985b). Specifically, we consider various possible managerial motives for choosing the timing of adoption of FAS No. 87 within the allowed period, and classify these motives as involving either compliance costs (the FASB's express justification for an extended adoption period) or investor perceptions (managers' attempts to change investor expectations). We then identify the adoption timing motives that are consistent with the data derived from samples of early (1986) and late (1987) adopters. The FASB's case for extending adoption periods will obviously be supported if compliance costs figure predominantly in firms' adoption-timing decisions. Of the eight proxies for adoption-timing motives examined by us, only one–increasing reported earnings–consistently discriminates between early and late adopters. This holds for interyear (1986 vs. 1987) as well as intrayear adoptions (first three quarters of 1986 vs. fourth quarter). Of the compliance-cost motives examined, company size and the number of outstanding loans were associated with the adoption-timing decision in some cases. Overall, our analysis does not provide compelling support for the FASB's cost-reduction justification for a multiyear adoption period for FAS No. 87.